Dampak Media Sosial dalam Cyber Bullying - Monica Hidajat; Angry Ronald Adam; Muhammad Danaparamita; Suhendrik Suhendrik (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The purpose of this research is to review two journals about social media effect for cyberbullying. First Journal is written by Eddie Fisher with the title From Cyber Bullying to Cyber Coping: The Misuse of Mobile Technology and Social Media and Their Effects on People’s Lives and the second journal is written by ReginaldH. Gonzales with the title Social Media as a Channel and its Implications on Cyber Bullying. First Journal focus on condition and cyber bullying state by interview respondents in law terms. Second journal focus on handling cyber bullying case at social media. Social medial cause few cases of cyberbullying increasing because of its characteristic that possible to spread information easily and fast. Socialization proper use of social media needs to be done to improve public awareness about the dangers of misuse of social media.